Space syntax as a tool for analyzing urban occupation: A study in southern Brazil - Tochetto , Fernanda; Neckel, Alcindo; Silva, Caliane Christie Oliveira de Almeida; Schmitz, Guilherme Peterle (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The lack of planning and effective housing policies has encouraged the search for housing in informal settlements, generally located on the outskirts of cities and segregated by urban sprawl. Space syntax is an important tool for analyzing urban configuration, allowing us to understand the geographical space as a whole, with its limitations and potential, capable of understanding the levels of integration and segregation, improving its flow and connectivity possible. This article analyzes connectivity and integration, using the spatial syntax of vulnerable occupation areas in the city of Erechim/RS (southern Brazil). This study was divided into five stages: a) bibliographical research; b) identification of the areas of occupation in Erechim; c) preparation of an axial map of the city; d) axial analysis using the Detphtamp 0.50 software and, finally; e) cross-referencing the information using the Qgis software. We identified the presence of occupations in green areas, mostly on the outskirts of the city, segregated to the other regions of the city, with a general average integration of 1.514 pixels, where the areas with the best economic value (between 1,720.01 and 5,231.01 reais) have the best connectivity.